Jonction syntaxique et formalité du contexte - Anne‑Marie Bezzina (Multilinguales)
Context is a continuously changing reality in a verbal exchange. In this article, an analysis is made of how intraspeaker variation functions as a contextualisation cue in situations marked by different degrees of formality, through a study of clause junction patterns. The distinction between institutional and individuals’ formality determines the corpus participant configuration. There is a high level of clause integration through subordination in institutional contexts, but other language features rather than subordination characterize individuals’ non-institutional formality. Clause junction appears to be a sign of a stylistic variation realized through register, inherent to the Maltese language.